Binding of Features and Responses in Inhibition of Return: The Effects of Task Demand - Hsuan-Fu Chao; Fei-Shan Hsiao; Shih-Ching Huang (Journal of Cognition, 2022)
Binding of target’s location and response has been demonstrated in inhibition of return (IOR). This study further investigated the effects of task demand on the binding of the target’s form to the target’s location and response in the target-target paradigm of IOR. Experiments 1 (detection task) and 2 (localization task), in which the target’s form was task irrelevant, suggested the binding of location and response. Experiment  3 (discrimination task), in which the target’s form was task relevant, showed the binding of target’s form, location, and response. These findings support the concept that the features and responses associated with a target are integrated into episodic representations or event files for the target event. Furthermore, task demand modulates the binding or retrieval of the event files.